Towards Harmonious Religious Interaction: An Educational Analysis of H. M. Rasjidi’s Thoughts on Islam and Christianity - Mohammad Zakki Azani; Mohamad Ali (TSAQAFAH, 2025)
The article focuses on H. M Rasjidi’s thoughts and experiences with regard to the relation and dialogue between Muslims and Christians in Indonesia. Rasjidi's works seriously discuss the historical events and intellectual debates pertaining to Muslim-Christian conflicts in Indonesia. Furthermore, this article discusses the methods for engaging with other faiths in both Islam and Christianity. Discussing a brief understanding of the established principles in Islam as a framework for a dialogue with other faiths shall be done first. Using this framework, Rasjidi scrutinizes the Christian principles of respecting other faiths through Christian congresses and literature, aiming to address social problems. Since Rasjidi, in many of his works, has been dedicated to clarifying problems concerning Muslim-Christian relationships, this article shall be an interesting topic in this research to know how Rasjidi tries to explain the relationship between Islam and Christianity in Indonesia.